2018
DOI: 10.1038/s41591-018-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptionally and functionally distinct PD-1+ CD8+ T cell pool with predictive potential in non-small-cell lung cancer treated with PD-1 blockade

Abstract: Evidence from mouse chronic viral infection models suggests that CD8+ T cell subsets characterized by distinct expression levels of the receptor PD-1 diverge in their state of exhaustion and potential for reinvigoration by PD-1 blockade. However, it remains unknown whether T cells in human cancer adopt a similar spectrum of exhausted states based on PD-1 expression levels. We compared transcriptional, metabolic, and functional signatures of intratumoral CD8+ T lymphocyte populations with high (PD-1T), intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

66
750
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 863 publications
(885 citation statements)
references
References 56 publications
66
750
8
2
Order By: Relevance
“…Although we have focused on MitoTracker® dyes in this report, objective gating could be used to gate populations stained with other mitochondrial dyes, and with other fluorescent antibodies or cellular dyes where delineating “high” and “low” populations is challenging. For example, multiple studies have reported differences in function and response to immunotherapy between PD‐1 “high” and PD‐1 “intermediate” or “low” T cells, but as yet there is no standardized method for identifying these different populations . As we have demonstrated, the method can be modified to gate, for example, cells in the top 50% of the fluorescence range, according to the requirements of the researcher.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have focused on MitoTracker® dyes in this report, objective gating could be used to gate populations stained with other mitochondrial dyes, and with other fluorescent antibodies or cellular dyes where delineating “high” and “low” populations is challenging. For example, multiple studies have reported differences in function and response to immunotherapy between PD‐1 “high” and PD‐1 “intermediate” or “low” T cells, but as yet there is no standardized method for identifying these different populations . As we have demonstrated, the method can be modified to gate, for example, cells in the top 50% of the fluorescence range, according to the requirements of the researcher.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding is that 4‐1BB was almost exclusively expressed on PD‐1 high CD8 + TILs, which reportedly represent highly exhausted and tumor‐reactive CD8 + TILs . We recently demonstrated that PD‐1 high CD8 + TILs exhibit features of more progressed T‐cell exhaustion compared to PD‐1 int and PD‐1 neg CD8 + TILs and that HCCs with higher proportions of PD‐1 high CD8 + TILs are enriched for the T‐cell–inflamed gene signature .…”
Section: Discussionmentioning
confidence: 92%
“…We recently demonstrated that PD‐1 + CD8 + TILs from HCC patients can be subdivided into PD‐1 int and PD‐1 high CD8 + TILs and that the latter group shows features of more‐severe T‐cell exhaustion . Another recent study found that PD‐1 high CD8 + TILs exhibit high tumor reactivity . Therefore, we next examined 4‐1BB expression on CD8 + TILs according to differential PD‐1 expression, to investigate the role of 4‐1BB in the context of T‐cell exhaustion and tumor reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations